Hubungan Kecemasan Matematika dengan Minat Belajar Siswa Kelas V SDN Gendingan 1 - Syaharani, Nur Affifah; Permata, Santy Dinar; Rahmawati, Arum Dwi (Civiliza Publishing, Indonesia., 2023)
Mathematics anxiety is a form of feeling anxious, afraid, and tense when facing mathematics problems or learning mathematics. Mathematics anxiety has an impact on students' interest in learning mathematics. Based on observations during mathematics learning, many students do not pay attention to the teacher when explaining the material, are noisy with their friends, cannot do the problems given by the teacher and do not dare when appointed to come forward to work on problems on the board. This is an indicator that students experience mathematics anxiety, resulting in a lack of interest in learning mathematics in class V of SDN Gendingan 1. This type of study is a correlational study that applies quantitative methods. The population subjects in this study were 40 students from class V at SDN Gendingan 1. To select a sample, the method used was the cluster random sampling technique. The data collection method involved the use of an instrument in the form of a questionnaire about anxiety in mathematics and learning interest. The results of the simple paired T-test analysis showed that the significance value was 0.00, which was less than 0.05. Therefore, H₁ was accepted while H₀ was rejected. This means that there is a relationship between mathematics anxiety and students' learning interest. The results of the person product moment correlation test have a value of 0.549 (moderate category). The determination coefficient approach of 30.25% indicates that about 30.25% of the variation in students' learning interest can be explained by the level of mathematics anxiety.